Structural Lessons From the Mutant Proinsulin Syndrome - Dhayalan, Balamurugan; Chatterjee, Deepak; Chen, Yen-Shan; Weiss, Michael A. (Frontiers in Endocrinology, 2021)
Insight into folding mechanisms of proinsulin has been provided by analysis of dominant diabetes-associated mutations in the human insulin gene (INS). Such mutations cause pancreatic -cell dysfunction due to toxic misfolding of a mutant proinsulin and impairment in trans of wild-type insulin secretion. Anticipated by the “Akita” mouse (a classical model of monogenic diabetes mellitus; DM), this syndrome illustrates the paradigm endoreticulum (ER) stress leading to intracellular proteotoxicity. Diverse clinical mutations directly or indirectly perturb native disulfide pairing leading to protein misfolding and aberrant aggregation. Although most introduce or remove a cysteine (Cys; leading in either case to an unpaired thiol group), non-Cys-related mutations identify key determinants of folding efficiency. Studies of such mutations suggest that the hormone’s evolution has been constrained not only by structure-function relationships, but also by the susceptibility of its single-chain precursor to impaired foldability. An intriguing hypothesis posits that INS overexpression in response to peripheral insulin resistance likewise leads to chronic ER stress and -cell dysfunction in the natural history of non-syndromic Type 2 DM. Cryptic contributions of conserved residues to folding efficiency, as uncovered by rare genetic variants, define molecular links between biophysical principles and the emerging paradigm of Darwinian medicine: Biosynthesis of proinsulin at the edge of non-foldability provides a key determinant of “diabesity” as a pandemic disease of civilization.